TWO PHASE GAS-LIQUID FLOWS RECOGNITION USING FUZZY INFERENCE - Fiderek, Paweł; Wajman, Radosław; Kucharski, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
In this paper the authors shows the new methodology of two phase gas-liquid flows recognition based on the fuzzy inference. At the beginning there is a short description of the experimental set up, later there is a detailed description of the experimental data processing and analysis algorithm and the fuzzy rules building routine, at the end of this paper there are the research results and analysis.